Analisis Manajemen Strategi PT Bank Central Asia Tbk Menjaga Dominasi CASA dengan Pendekatan SWOT, SPACE, BCG, IE Matrix, dan Grand Strategy Matrix - Lintar Novianti Watanaya (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the strategic management of PT Bank Central Asia Tbk in maintaining its dominance in the Current Account Savings Account (CASA) segment amid increasingly intense competition in Indonesia’s banking industry. The analysis employs several strategic management tools, including PEST analysis, Porter’s Five Forces, Value Chain analysis, TOWS Matrix, SPACE Matrix, BCG Matrix, IE Matrix, Grand Strategy Matrix, and QSPM, to identify the bank’s internal and external strategic position and formulate appropriate strategic alternatives. The results indicate that the bank possesses strong financial performance, high liquidity, efficient operational capabilities, and advanced digital innovation that support its competitive advantage. The CASA segment functions as a key pillar in sustaining low-cost funds and strengthening profitability. The recommended priority strategy is market development, particularly through expanding services to micro and rural segments, strengthening digital ecosystems, and collaborating with fintech to capture new growth opportunities. This study contributes to a deeper understanding of how digital transformation, customer-centric services, and strategic market expansion can sustain competitive advantage in a mature and highly regulated banking industry